Catch-quota balancing mechanisms in the Icelandic multi-species demersal fishery: Are all species equal?. (May 2015) - Woods, Pamela J.; Bouchard, Caroline; Holland, Daniel S.; Punt, André E.; Marteinsdóttir, Guðrun
Abstract: In this study, utilization of catch-quota balancing mechanisms in the Icelandic demersal fishery, which allow for individual transferable quota to be transformed among species and transferred between years, is analyzed to determine whether annual catches closely adhere to total allowable catches on average. Icelandic landings data for 14 demersal fish species during 2001–2013 are compared to implemented total allowable catches as well as catch limits recommended by the Marine Research Institute (MRI) and a proxy for annual market values. Landings surpassed legal limits of total allowable catch in 27% of the cases (landings by species by fishing year), mostly due to species transformations, but TAC overages were not consistent for any species. Instead, catches of some species were consistently less than legal limits, with some indications that landings were related to profitability (i.e. landings were correlated with market value). However, landings surpassed MRI recommendations in 67% of the cases, and landings of four species (Atlantic wolffish, haddock, monkfish and redfish) consistently exceeded MRI recommendations. Therefore, discrepancies between scientific recommendations for catch limits and quotas selected through the political process may represent a higher risk to long-term sustainability than catch-quota balancing mechanisms. Highlights: Usage of catch-quota balancing mechanisms were analyzed in Icelandic fisheries. Some catches of the 14 species were highly variable or correlated with market value. Although used often 2001–2013, they did not cause systematic excessive fishing. Instead, not following scientific advice is more likely to threaten sustainability.